2014
DOI: 10.1111/ppl.12248
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced chloroplastic generation of H2O2 in stress‐resistant Thellungiella salsuginea in comparison to Arabidopsis thaliana

Abstract: In order to find some basis of salinity resistance in the chloroplastic metabolism, a halophytic Thellungiella salsuginea was compared with glycophytic Arabidopsis thaliana. In control T.s. plants the increased ratios of chlorophyll a/b and of fluorescence emission at 77 K (F730/F685) were documented, in comparison to A.t.. This was accompanied by a higher YII and lower NPQ (non-photochemical quenching) values, and by a more active PSI (photosystem I). Another prominent feature of the photosynthetic electron t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 46 publications
4
30
0
1
Order By: Relevance
“…Our recent data point to a much higher generation of H 2 O 2 by PET in T. halophila in comparison to A. thaliana (Wiciarz et al 2014). Similarly, in leaves of S. salsa the level of H 2 O 2 was found to be lower after salinity than in control conditions .…”
Section: Antioxidants and Role Of Rosmentioning
confidence: 79%
See 2 more Smart Citations
“…Our recent data point to a much higher generation of H 2 O 2 by PET in T. halophila in comparison to A. thaliana (Wiciarz et al 2014). Similarly, in leaves of S. salsa the level of H 2 O 2 was found to be lower after salinity than in control conditions .…”
Section: Antioxidants and Role Of Rosmentioning
confidence: 79%
“…Despite that, Rubisco appeared to be more highly activated in vitro (Davies and Griffiths 2012). Our recent study made on T. halophila revealed that a majority of RCA is attached to the thylakoid membranes, in contrast to A. thaliana where the soluble form is predominant (Wiciarz et al 2014). This is associated by a higher Rubisco activation state in the former species.…”
Section: Rubisco Activity and Activationmentioning
confidence: 82%
See 1 more Smart Citation
“…3). There are different possibilities for the generation of H 2 O 2 within plant cells under different conditions (Wiciarz et al, 2015). To our data, under Cd stress illuminated cells produce higher levels of H 2 O 2 than dark-adapted cells (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…The thylakoids were isolated as described by Wiciarz, Gubernator, Kruk, and Niewiadomska (2015), and their activity was measured as the rate of oxygen evolution/consumption using a Clark-type oxygen electrode (Oxytherm, Hansatech, UK). The total electron transport activity was tested by applying 1 mM K 3 [Fe (CN) 6 ] as the electron acceptor, whereas the PSII activity was measured using 0.1-mM 2,6dichloro-1,4-benzoquinone.…”
Section: Measurements Of Thylakoid Electron Transport Activitymentioning
confidence: 99%